Un malestar llamado libro. Poamorio de Canton y otros experimentos - Julio Schvartzman (Cuadernos LIRICO)
The Dario Canton’s book of poems Poamorio produces from the very beginning a morpholexical transformation –a pun that moves the Spanish word meaning “poems collection” (poemario) to a neologism where the love object takes the place of the whole genre. At the same time, its support completes a disconcerting mutation, producing defamiliarization: is this a book? And if it is, how to catalogue it? The object resists the bibliographical classification. Which are its limits? “Attempt to deny itself as an object” –as Héctor Schmucler defined it in Los Libros, the Canton´s experiment took place while Julio Cortázar made his Último round known and in a decade that started with Raymond Queneau’s Cent mille milliards de poèmes (1961) whose mock-up created by Robert Massin graphically met the combinatory procedure required by the potential literature aims. That games were posing an unease and a series of requirements that would only be resolved a few decades after, through new technologies of writing and reading, including digital hypertext.